2019
DOI: 10.1101/836148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial and temporal patterns of nitric oxide diffusion and degradation drive emergent cerebrovascular dynamics

Abstract: Nitric oxide (NO) is a gaseous signaling molecule that plays an important role 1 in neurovascular coupling. NO produced by neurons diffuses into the smooth muscle 2 surrounding cerebral arterioles, driving vasodilation.However, the rate of NO 3 degradation in hemoglobin is orders of magnitude higher than in brain tissue, though how 4 this might impact NO signaling dynamics is not completely understood. We used 5 simulations to investigate how the spatial and temporal patterns of NO generation and 6 degradation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 219 publications
(287 reference statements)
0
4
0
Order By: Relevance
“…Another possibility could be the spatial location of the generation of the vasodilator(s) relative to the arterioles, particularly in the case of nitric oxide. Simulation of NO diffusion and degradation dynamics in the tissue have shown that NO production needs to be very close (of order microns to tens of microns) to the arteriole in order to exert an appreciable dilatory effect ( Haselden et al, 2020 ). It could be that NO is produced closer to pial vessel (potentially in the processes of more superficial type two neurons), than near the penetrating arterioles in the superficial layers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility could be the spatial location of the generation of the vasodilator(s) relative to the arterioles, particularly in the case of nitric oxide. Simulation of NO diffusion and degradation dynamics in the tissue have shown that NO production needs to be very close (of order microns to tens of microns) to the arteriole in order to exert an appreciable dilatory effect ( Haselden et al, 2020 ). It could be that NO is produced closer to pial vessel (potentially in the processes of more superficial type two neurons), than near the penetrating arterioles in the superficial layers.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have shown that activation of Substance P receptors drives large increases in activity ( Endo et al, 2016 ; Williams et al, 2019 ; Williams et al, 2018 ), potentially accounting for the asymmetry of vascular responses to the application of blockers and activators of these receptors. Simulations have shown that the location of NO production relative to the arteriole has a large impact on its efficacy ( Haselden et al, 2020 ), so the location of the infected neurons relative to the arterioles may cause some variability. We performed our experiments in awake mice, as anesthetics cause large decreases in brain metabolism, cardiovascular output, and ongoing neural activity ( Gao et al, 2017 ), but there could be some variability associated with the mice being awake.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed the possibility of using the fractional flow-mediated dilatation (FFMD) parameter to differentiate the endothelial function between young and middle age groups. Also, in another study, Haselden et al [34] showed that both the spatial location of NO production and the size of the vessel play an important role in determining its response to NO. They also showed that changes in blood flow during hypoxia or hyperoxia could indicate a decrease in NO in the parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…This coupling between neural activity and hemodynamics is known as neurovascular coupling (NVC) 12 . While there are many successful phenomenological models of NVC 3,[13][14][15][16][17] , most physiology-based models of neurovascular coupling [18][19][20][21] focus on a single mechanism. As NVC is mediated through multiple processes, a more integrated approach is necessary.…”
Section: Introductionmentioning
confidence: 99%